2017
DOI: 10.1016/j.virusres.2016.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Valosin-containing protein (VCP/p97) plays a role in the replication of West Nile virus

Abstract: Valosin-containing protein (VCP) is classified as a member of the type II AAA(+) ATPase protein family. VCP functions in several cellular processes, including protein degradation, membrane fusion, vesicular trafficking and disassembly of stress granules. Moreover, VCP is considered to play a role in the replication of several viruses, albeit through different mechanisms. In the present study, we have investigated the role of VCP in West Nile virus (WNV) infection. Endogenous VCP expression was inhibited using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 81 publications
3
29
0
Order By: Relevance
“…Although we have illustrated free nucleocapsids within the cytosol, we cannot exclude the possibility that fusion is tightly coupled to capsid ubiquitylation and disassembly, such that nucleocapsids may be ubiquitylated and disassembled as they are exposed to the cytosol. Consistent with our model, VCP/p97 activity was previously shown to be important for WNV, JEV, and DENV infection, although specific role(s) for VCP/p97 in virus entry were not determined (53,83). Similarly, VCP/p97 is also important for an early step, upstream of N-protein degradation, during the entry of infectious bronchitis virus, a coronavirus (84).…”
Section: Discussionsupporting
confidence: 82%
“…Although we have illustrated free nucleocapsids within the cytosol, we cannot exclude the possibility that fusion is tightly coupled to capsid ubiquitylation and disassembly, such that nucleocapsids may be ubiquitylated and disassembled as they are exposed to the cytosol. Consistent with our model, VCP/p97 activity was previously shown to be important for WNV, JEV, and DENV infection, although specific role(s) for VCP/p97 in virus entry were not determined (53,83). Similarly, VCP/p97 is also important for an early step, upstream of N-protein degradation, during the entry of infectious bronchitis virus, a coronavirus (84).…”
Section: Discussionsupporting
confidence: 82%
“…Mutations in the sequences of the C protein or structural proteins of WNV were introduced via inverse PCR. The plasmid expressing envelope protein prME (pCXSN-prME) and the plasmid expressing the subgenomic RNA of WNV (pCMV-WNrep-DsRed) were previously constructed [18,49]. The plasmid expressing the NS proteins (pWNIIrep-GFP, was generously provided by Dr. Robert W. Doms) was previously constructed [50].…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…Rabbit anti-JEV serum that exhibited cross-reactivity with the WNV E protein was produced as previously described [51]. Rabbit anti-NS3 serum was prepared as previously described [49]. The following antibodies were purchased: mouse anti-WNV E protein monoclonal antibody (Merck Millipore, Billerica, MA, USA); mouse anti-ubiquitin monoclonal antibody (Enzo Life Sciences Inc., Farmingdale, NY, USA); mouse anti-actin monoclonal antibody (Wako); mouse anti-LC3 monoclonal antibody, rabbit anti-DDDDK-tag, anti-LC3 and anti-p62 polyclonal antibodies (MBL, Nagoya, Japan); and rabbit anti-AMPK polyclonal and monoclonal antibodies (Cell Signaling Technology, Beverly, MA, USA).…”
Section: Antibodies Reagents and Transfectionmentioning
confidence: 99%
“…reported that VCP participated in viral genome replication of poliovirus, hepatitis C virus and West Nile virus (Arita et al, 2012;Phongphaew et al, 2017;Yi et al, 2016). In addition, roles of VCP in early stages of viral infection have been reported for Coronavirus and Sindbis virus (Panda et al, 2013;Wong et al, 2015).…”
Section: Discussionmentioning
confidence: 99%